High Redundancy Actuator with 12 Elements: Open- and Closed-loop Model Validation. Issue 21 (2016) - Antong, Hasmawati; Dixon, Roger; Ward, Christopher P.
Abstract: The high-redundancy actuator concept that is inspired by biomimetic is an approach to fault tolerant actuator that aims to provide fault tolerance using relatively large numbers of small actuation elements. The actuation elements are assembled in parallel and series configurations to form a single actuator that has intrinsic fault tolerance. During normal operations, it is possible that some of these elements are operational and some are faulty. In this situation, the high-redundancy actuator will still work, but with graceful degradation. This paper discusses the modelling aspect of the high-redundancy actuator that consists of 12 actuation elements based on linear electromechanical actuation technology. Simulation results are validated with real-time experimental results using both a single actuator and the full high-redundancy actuator in open-loop and closed-loop.